INDRAPRASTA (Indoor Disaster Simulation For Interprofessional Education) with Tabletop Disaster Exercise (TDE) in disaster management for health students to enhace Interprofessional Education (IPE) - Maryana, Maryana; Handayani, Tri Widyastuti; Nugroho, Arif Riyanto Budi; Rahmani, Septi Ayu; Syafa, Luthfiani (MEDIA ILMU KESEHATAN, 2024)
Background: The earlier integration of IPE in the clinical environment makes students explore the roles and responsibilities of each profession through active learning. One application of IPE learning in disaster management can be applied with the Tabletop Disaster Exercise (TDE) method, this can help students develop IPC skills between health professionals and is very important to apply in managing critical condition situations. Objective: This study aims to determine the effect of the application of TDE in the readiness of IPE learning on students of Poltekkes Kemenkes Yogyakarta.Methods: This research is a quasi experimental research. The research was conducted in June-August 2024 at the Poltekkes Kemenkes Yogyakarta. The sample size was 96 students, taken using purposive sampling. Results: There is a difference in readiness level between pre-test and post-test among respondents after TDE intervention (p value=0.000). There is a difference in the level of knowledge between pre-test and post-test among respondents after TDE intervention (p value=0.000).Conclusion: From the result of this research can be concluded that the application of TDE can have a significant effect on the readiness of IPE learning in health students of the Poltekkes Kemenkes Yogyakarta.